Hubungan Body Mass Index dengan Laju Aliran Saliva (Studi pada Mahasiswa Fakultas Kedokteran Gigi Universitas Andalas) - Fildzah Nurul Fajrin; Zulkarnain Agus; Nila Kasuma (Majalah Kedokteran Gigi Indonesia, 2015)
Relationship between Body Mass Index and Saliva Flow Rate (A Study in Faculty of Dentistry, Andalas University). Saliva flow rate is an affecting factor of caries formation. Adequate saliva flow rate can prevent cariess formation process and progression of periodontal disease and oral infection. Nutritional status is known as an influencing factor of saliva flow rate. The parameter of nutritional status is Body Mass Index (BMI). The purpose of this study is to discover the relation between BMI and saliva flow rate in College Students of the Dentistry Faculty Andalas University. This observational study with cross sectional design was conducted to 24 college students of the Dentistry Faculty Andalas University whose ages were 18-25 years old who complied with inclussion and exclussion criteria. BMI was calculated with BMI formula. The saliva flow rate was determined with Sialometry Method of Navazesh 2008 with ”ml/minute” unit. The univariat data analysis was caried out to describe each variable. Normality test Kolmogorov Smirnoff was done to see the normal distribution (p > 0,05). After the distribution was proven to be normal, corelation and regression test was executed to discover the relation between BMI and saliva flow rate. Based on the correlation test result, BMI of college students of the Dentistry Faculty Andalas University is χχ ± SD = 24,6 ± 6,02 kg/m2 and saliva flow rate is χχ ± SD = 0,29 ± 0,1 ml/minute. The relation between BMI and saliva flow rate expresses medium correlation with negative direction ( r = - 0,451). The result of linear regression shows that Saliva Flow Rate = 0,404 - 0,008*(BMI). The coefficient of regression BMI 0.008 shows that increasing 1 unit of BMI will decrease saliva flow rate 0,008 ml/minute. This study concludes that there is correlation between Body Mass Index and saliva flow rate. Obesity group has the lowest saliva flow rate, while the saliva flow rate does not decrease in underweight group.